(3GdJShjI h GdJaGhV aj bGfhf GdELQGAGJ GdLfGFjI (B: s (3OQGSI ebGQfI (B/ s - (3aQOhS GdQhTjs; (3eOMJ YHOGdMdje QeVGf (B: s ((3GdbGgQI (B: s (3aQOhS GdQhTj (B: s, 2013)
(3JYJHQ OQGSI GdJShjI GdLfGFjI h GdJaGhV aj bGfhf GdELQGAGJ GdLfGFjI hGMOI ef Cge GdehVhYGJ GdJj YQaJ JYOjdGJ h EUdGMGJ aj eNJda GdJTQjYGJ GSJLGHI Edi Ndb ELQGAGJ SQjYI h eHSWI eMd GdELQGAGJ GdLfGFjI GdYGOjI h Pdc ef CLd Md GdLQGFe PGJ GdLSGeI GdeMOhOI h GdJj CUHMJ JYhb LdSGJ GdeMGce (B. (3h JYGdL GdQSGdI ehVhY GdJShjI h GdJaGhV aj bGfhf GdELQGAGJ GdLfGFjI aj bSejf (B: (3CeG GdbSe GdChd aNUU dOQGSI GdJShjI GdLfGFjI ef NdGd HGHjf (B: (3GdChd dJMOjO eG gjI GdJShjI (B: (3h GdKGfj ddMOjK Yf ELQGAGJgG (B. (3CeG GdbSe GdKGfj aYQV ajg GdJaGhV Ydi GdGYJQGa aj bGfhf GdELQGAGJ GdaQfSjs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJShjI GdLfGFjIs; (3GdJUGdM GdLfGFjs; (3GdJaGhV Ydi GdGYJQGas